Enhanced AOX accumulation and aquatic toxicity during 2, 4, 6-trichlorophenol degradation in a Co(II)/peroxymonosulfate/Cl− system. (February 2016) - Fang, Changling; Xiao, Dongxue; Liu, Wenqian; Lou, Xiaoyi; Zhou, Jun; Wang, Zhaohui; Liu, Jianshe
Abstract: Chloride ion is known to affect on degradation kinetics in different ways during HO and SO 4 APTARANORMAL − -based advanced oxidation processes (AOPs). However, its effect on absorbable organic halogen (AOX) evolution and acute toxicity of treated water remains unknown, despite the importance of the two parameters in evaluating the applicability of AOPs. In the present study, Co/peroxymonosulfate (Co/PMS) and UV/hydrogen peroxide (UV/H2 O2 ) treatment of 2, 4, 6-trichlorophenol was compared in terms of AOX formation, chlorinated byproducts and acute toxicity. Both Co/PMS and UV/H2 O2 systems were more reactive under acidic conditions, resulting in elevated AOX levels when compared with those at neutral pH. The presence of high levels of chloride led to an accumulation and increase of AOX in the Co/PMS system. The toxicity of chlorinated byproducts was evaluated using Photobacterium phosphoreum, and the results revealed a sharp increase in acute toxicity of Co/PMS reaction solutions on addition of chloride ion. However, addition of Cl − had no apparent impact on AOX and toxicity of UV/H2 O2 reaction solutions. These findings may have significant technical implications for selecting feasible technologies to treat high salinity wastewater. Graphical abstract: Highlights: An increase in AOX was observed when adding chloride ions in Co/PMS system. Cl − concentration and pH largely affected the formation of AOX. The presence of chloride led to an increase in acute toxicity in Co/PMS system. PMS-based AOPs are not recommended to used in saline wastewater treatment.